53. PATIENT SATISFACTION WITH THE QUALITY OF MEDICAL SERVICES AT THE DEPARTMENT OF PHYSICAL MEDICINE AND REHABILITATION, HUE UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To assess outpatient satisfaction with the quality of medical services at the Department of Rehabilitation, Hue University of Medicine and Pharmacy Hospital.Method: A cross-sectional descriptive study was conducted on 400 outpatients using the survey tool issued under Decision No. 3869/QD-BYT. Data were analyzed using SPSS 20.0.Results: The overall satisfaction rate was 84.4%. The highest-rated aspect was “attitude and professional competence of medical staff” (92.9%), while the lowest was “transparency of information and administrative procedures” (80%). The rate of comprehensive satisfaction was 25.5%. Notably, 89.5% of patients stated they would definitely return or recommend the service to others.Conclusion: Patients were generally satisfied with the service quality. However, further improvements in administrative procedures, waiting time, and service accessibility are needed to enhance comprehensive satisfaction.
Keywords: Satisfaction; patient; rehabilitation; healthcare service quality.